AKTIVITAS ANTIRADIKAL DPPH SERTA PENENTUAN KANDUNGAN FENOLIK DAN FLAVONOID TOTAL SARI LARUT AIR DAUN DAN BUAH Ficus carica L. DAN Ficus parietalis Bl. - Oktavia Tri Wahyuni; Triana Hertiani (Faculty of Pharmacy, Universitas Gadjah Mada, 2016)
Ficus carica L and Ficus parietalis Bl. (Moraceae) are closely related plants which also known in Indonesia as Figs L. Considering the wide therapeutic value of Figs, this research was aimed to evaluate the DPPH-radical scavenging activity of both plants as well as their total phenolic and flavonoids. Extracts were produced by using boiled water and diluted to gain the desired concentration. Analyses were performed by using UV-vis spectrophotometer. Radical scavenging activity testing was done by using radical of DPPH (2,2-diphenyl-1-pycrylhydrazyl) to determine the IC50s. The determination of total phenolic was conducted by using Folin-Ciocalteau method and calculated as Gallic Acid Equivalence (GAE). The total flavonoid was measured by using AlCl3-reagents, and calculated as Rutin Equivalence (RE). Afterwards, the radical scavenging activity was correlated to the total phenolic and flavonoids contents. The results showed that the water soluble extract of F. carica fruit had the best IC50 value of 33.38 mg/mL, followed successively by the F. parietalis fruit (35.69 mg/mL), F. parietalis leaves (44.01 mg/mL) and the F. carica leaves (76.38 mg/mL). The highest content of total phenolic was shown by the leaves of F. parietalis (1.46% w/w GAE) and the lowest was in the fruit or F. carica (0.36% w/w GAE). The highest flavonoid content was detected in the leaves of F. carica (1.42% w/w RE) and the lowest was in the F. parietalis fruit (0.20% w/w RE). Correlation analyses of the IC50 values vs. the total phenolic and the flavonoids contents resulted in a positive slope having R2 values as 0.5362 and 0.9895, respectively. As a conclusion, the total flavonoid content influenced the DPPH radical scavenging activity by 98.95%, while the total phenolic content influence was only 53.62%.